Analysis of dependence of primary brain-growth occurrence on solar cycle - B. N. Bein; V. F. Kochmashev; Ye. V. Kondratiyeva; M. V. Mukhacheva (Бюллетень сибирской медицины)
Taking medical documents as a basis we’ve set up the guantity of registered of primery brain’s tumour (BT) for the period of 1966—2005 years. The data were compared with the published accounts about the average guantity of solar spots, which reflects the level of solar activity. Mathematic analysis registered some parallels of dynamic summery freguency of all varieties of brain’s tumour (BT) and the quantity of solar spots , so that the changing of tumour’s graphic 4—5 years behind. The lagging of the curve of solar activity - sometimes as far a half of the 11 years cycle — refers only to benign tumour. Changing of the level of malignant tumour closely follows the solar activity index and have line interaction which depends on solar spots.